Sc3N@Ih-C80 based donor–acceptor conjugate: role of thiophene spacer in promoting ultrafast excited state charge separation. Issue 34 (27th May 2020) - Caballero, Rubén; Servián, Luis David; Gobeze, Habtom B.; Fernandez-Delgado, Olivia; Echegoyen, Luis; D'Souza, Francis; Langa, Fernando
Abstract : Photoinduced charge separation and dark charge recombination occurring within picoseconds is observed in newly synthesized triphenylamine–thiophene-Sc3 N@ I h -C80 and triphenylamine–thiophene-C60 conjugates. Abstract : Light induced charge separation in a newly synthesized triphenylamine–thiophene-Sc3 N@ I h -C80 donor–acceptor conjugate and its C60 analog, triphenylamine–thiophene-C60 conjugate is reported, and the significance of the thiophene spacer in promoting electron transfer events is unraveled.